Targeting Wnt/Beta-Catenin Signaling in HPV-Positive Head and Neck Squamous Cell Carcinoma - Faris F. Brkic; Stefan Stoiber; Tobias Maier; Elisabeth Gurnhofer; Lukas Kenner; Gregor Heiduschka; Lorenz Kadletz-Wanke (MDPI AG, 2022)
Wnt/Beta-Catenin signaling is involved in the carcinogenesis of different solid malignant tumors. The interaction of Creb-binding protein (CBP) with Beta-Catenin is a pivotal component of the Wnt/Beta-Catenin signaling pathway. The first aim of this study was to evaluate the association of CBP expression with survival in patients with human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC). Second, the in vitro effects of the inhibition of CBP/Beta-Catenin interaction were analyzed. In particular, the effects of ICG-001, an inhibitor of CBP/Beta-Catenin interaction, on proliferation, cell death, modulation of Wnt/Beta-Catenin target expression, and cell migration were examined in vitro. High CBP expression is significantly associated with better survival on mRNA and protein levels. Furthermore, we observed cytotoxic as well as anti-migratory effects of ICG-001. These effects were particularly more potent in the HPV-positive than in the -negative cell line. Mechanistically, ICG-001 treatment induced apoptosis and led to a downregulation of CBP, c-MYC, and Cyclin D1 in HPV-positive cells, indicating inhibition of Wnt/Beta-Catenin signaling. In conclusion, high CBP expression is observed in HPV-positive HNSCC patients with a good prognosis, and ICG-001 showed a promising antineoplastic potential, particularly in HPV-positive HNSCC cells. Therefore, ICG-001 may potentially become an essential component of treatment de-escalation regimens for HPV-positive HNSCC. Further studies are warranted for additional assessment of the mechanistic background of our in vitro findings.